Molecular characterization of three digeneans parasitizing marine fish in the Gulf of Thailand - Suwannarat, Nannaphat; Gilardoni, Carmen; Ribas, Alexis; Miquel, Jordi; Poonlaphdecha, Srisupaph (Frontiers in Veterinary Science, 2025)
The Gulf of Thailand is a highly diverse marine ecosystem, yet knowledge of its helminth fauna remains fragmentary. Marine fishes were obtained in 2024 from accidental catches of crab-trap fishers or captured by local fishermen using boats in Chumphon Province, Thailand. In this study, we molecularly characterize three digenean trematode genera parasitizing marine fishes from this area: Lecithocladium (Hemiuridae) from the short mackerel (Rastrelliger brachysoma), with a prevalence of 77% in 22 fishes and ten worms examined for morphology; Prodistomum (Lepocreadiidae) from R.brachysoma, with a prevalence of 18% in 22 fishes, and from Rastrelliger kanagurta, with a prevalence of 100% in one fish, with 10 worms examined for morphology; and Lepocreadioides (Lepocreadiidae) from the double-lined tonguesole (Paraplagusia bilineata), with a prevalence of 75% in four fishes, and eight worms examined for morphology. Sequences of nuclear ribosomal markers (18S, ITS2, and 28S) were generated, providing the first molecular data for Lepocreadioides orientalis. Our analyses confirm the presence of Lecithocladium angustiovum and Prodistomum sp. in the Gulf of Thailand, contribute new molecular data, and provide a morphological description of Prodistomum sp. Despite the Gulf of Thailand’s high ichthyofaunal diversity, its helminth communities remain insufficiently investigated, highlighting the need for future research.